PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA THE BENE HOTEL KUTA - Kadek Arik Oktaviana Sari; I Made Sunata; I Ketut Eli Sumerta (Universitas Triatma Mulya, 2021)
This research is motivated by the phenomenon of employee morale in companies, especially in the field of tourism or hospitality. Employee morale is related to communication and the work environment, if communication is not effective, it will have an impact on the survival of the company, because the implementation of this communication cannot be separated from what has been felt by employees which in turn affects employee morale. The work environment has an important meaning, because without communication there will be no interaction between people in an organization, as well as the work environment. good. This study aims to analyze and prove the effect of communication and work environment on employee morale. This study uses a quantitative approach, which focuses on hypothesis testing using measured data so that it is hoped that a conclusion can be drawn. The sampling technique used is to use all members of the population as a sample so it is called census research. Multiple linear regression analysis using SPSS software version 23. The regression equation obtained is: Y = 2.280 + 0.430X1 + 0.457X2 + . The results of this study indicate that; firstly, communication has a positive and significant effect on employee morale, secondly the work environment has a positive and significant effect on employee morale and thirdly, communication and work environment have an influence of 64.7% on employee morale. some suggestions that can be given in this research include; improve communication in order to avoid misunderstandings and increase the comfort of the environment where employees work.